Persepsi Karyawan terhadap Emotional, Job Insecurity dan Well-Being di PDAM Kota Bengkulu - Anderi Pebperiadi; Slamet Widodo; Paulus Sulluk Kananlua (Universitas Bengkulu, 2022)
Abstract: The objectives of this study are (1) analyze employee perceptions of emotional at Regional Water Companies, Bengkulu City, (2) analyze employee perceptions of job insecurity at Regional Water Companies, Bengkulu City, and (3) analyze employee perceptions of well-being at Regional Water Companies, Bengkulu City. This study used a quantitative descriptive method, the research respondents were 35 employees of Water Company Bengkulu City (permanent employees with Diploma education and above). General and Technical Directorate. Collecting data by distributing questionnaires, interviews and documentation studies, while data analysis used descriptive statistics. The results of the study show that employees' emotions lead to deep acting. These results indicate that the emotions displayed by employees match the demands of the job role. Employees in doing deep acting change their feelings in an effort to adjust to the emotional appearance contained in organizational rules. Perceptions of job insecurity with insecure assessments. Employee job insecurity is in the job aspect, namely promotion opportunities. Another aspect of job insecurity that is classified as high in terms of the possibility of negative changes in the overall work, is overshadowed by the possibility of changing the workplace. This is more to the insecurity, often due to work rotation problems (mutations). Perception of well-being with a judgment of well-being. This means that employees have a positive mental attitude such as being happy, having meaning in life, having positive relationships with others. With this feeling of comfort or happiness, it has a positive impact on employees and the organization. The dimension of life purpose is the dimension with the highest average value of the well-being variable. Keywords: Emotional, Job Insecurity, Well-Being. Abstrak: Tujuan penelitian ini adalah (1) menganalisis persepsi emosional karyawan pada PDAM Kota Bengkulu, (2) menganalisis persepsi karyawan terhadap job insecurity di PDAM Kota Bengkulu, dan (3) menganalisis persepsi karyawan tentang kesejahteraan. pada Perusahaan Daerah Air Minum Kota Bengkulu. Penelitian ini menggunakan metode deskriptif kuantitatif, responden penelitian adalah 35 pegawai PDAM Kota Bengkulu (pegawai tetap berpendidikan D3 ke atas). Direktorat Jenderal dan Teknis. Pengumpulan data dengan penyebaran kuesioner, wawancara dan studi dokumentasi, sedangkan analisis data menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa emosi karyawan mengarah pada akting yang mendalam. Hasil ini menunjukkan bahwa emosi yang ditampilkan karyawan sesuai dengan tuntutan peran pekerjaan. Karyawan dalam melakukan deep acting mengubah perasaannya dalam upaya menyesuaikan diri dengan penampilan emosional yang terdapat dalam aturan organisasi. Persepsi ketidakamanan kerja dengan penilaian tidak aman. Job insecurity karyawan terdapat pada aspek pekerjaan yaitu kesempatan promosi. Aspek lain dari job insecurity yang tergolong tinggi dalam hal kemungkinan perubahan negatif dalam pekerjaan secara keseluruhan, dibayangi oleh kemungkinan perubahan tempat kerja. Ini lebih kepada ketidakamanan, seringkali karena masalah rotasi pekerjaan (mutasi). Persepsi kesejahteraan dengan penilaian kesejahteraan. Artinya karyawan memiliki sikap mental yang positif seperti merasa bahagia, memiliki arti dalam hidup, memiliki hubungan yang positif dengan orang lain. Dengan adanya perasaan nyaman atau bahagia ini memberikan dampak positif bagi karyawan dan organisasi. Dimensi tujuan hidup merupakan dimensi dengan nilai rata-rata tertinggi dari variabel kesejahteraan. Kata kunci: Emosional, Job Insecurity, Kesejahteraan.